Tourism Competitiveness Improvement with Democracy in Spain, 1975-1995 - Tascón Fernández, Julio; Caruana de las Cagigas, Leonardo (Hispania Nova, 2024)
Hostelry competitiveness in Spain suffered a dramatic reduction due higher wage paid under the new Democratic Regime. This significant decrease involves the influence of the Pactos de la Moncloa (Parliamentary agreements) and also the Oil crisis of the 70’s. The absence, in general, of coordinated strategies among public and private sectors added to the failure of the policies focused in improve labor productivity within touristic firms are the main reasons of the phenomenon. Productivity convergence (σ and β convergence) by worker and touristic labor costs convergence (hotels and restaurants) are permitting to afford significant evidence on how this touristic competitiveness is improving his level after the so call transition up to the last government of Felipe González (1982- 1995). The supply-side analysis -company competitiveness- is the novelty of our contribution as this point of view is not generally considered.
Keywords: Competitiveness; Spaon; touristic industry; productivity